2004
DOI: 10.3189/172756404781814942
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional geometric measurements of snow microstructural evolution under isothermal conditions

Abstract: Snow, from its fall until its full melting, undergoes a structural metamorphism that is governed by temperature and humidity fields. Among the many possible mechanisms that contribute to snow metamorphism, those that depend only on curvature are the most accessible to modelling. In this paper, techniques of volume data analysis adapted to the complex geometry of snow are introduced and then applied to experimental tomographic data coming from the isothermal metamorphism of snow near 0°C. In particular, an adap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
117
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(124 citation statements)
references
References 26 publications
3
117
0
Order By: Relevance
“…[18] It has been observed that the ice structure of snow might exhibit an anisotropy [Flin et al, 2004] as a result of metamorphism dynamics under isothermal conditions. A different anisotropy naturally emerges from BD/KPZ solely as a result of the deposition process and irrespective of possible anisotropic crystal shapes.…”
Section: Anisotropy Of Density Correlations In New Snowmentioning
confidence: 99%
“…[18] It has been observed that the ice structure of snow might exhibit an anisotropy [Flin et al, 2004] as a result of metamorphism dynamics under isothermal conditions. A different anisotropy naturally emerges from BD/KPZ solely as a result of the deposition process and irrespective of possible anisotropic crystal shapes.…”
Section: Anisotropy Of Density Correlations In New Snowmentioning
confidence: 99%
“…Since 2001, research on snow by means of a cryo-stat is being performed. Coleou et al (2001) and Heggli et al (2011) imaged and measured snow in 3D, while Flin et al (2004) characterized the snow microstructural evolution under isothermal conditions. Kaempfer et al (2005) described a microstructural approach to model heat transfer in snow, while Pieritz et al (2004) modelled the micromechanics of snow.…”
Section:  Multi-scale Imagingmentioning
confidence: 99%
“…These images were obtained from controlled cold-room experiments (samples s-DFRG, s-RG0, s-RG1 measured by Flin et al (2004) during an isothermal metamorphism experiment; sample s-FC measured by Calonne et al (2011) during a temperaturegradient experiment) or field sampling (sample s-DF measured by Flin et al (2011) and samples s-FCDF and s-FCDH measured by Hagenmuller et al, 2013). All samples were scanned with X-ray absorption tomography after impregnation of the material with 1-chloronaphtalene .…”
Section: -D Image Data Setmentioning
confidence: 99%